A combination of cherry juice and cold water immersion does not enhance marathon recovery compared to either treatment in isolation: A randomized placebo-controlled trial - Difranco, Isabella; Cockburn, Emma; Dimitriou, Lygeri; Paice, Katherine; Sinclair, Scott; Faki, Tanwir; Hills, Frank A.; Gondek, Marcela B.; Wood, Alyssa; Wilson, Laura J. (Frontiers in Sports and Active Living, 2022)
Purpose Cherry juice (CJ) and cold water immersion (CWI) are both effective recovery strategies following strenuous endurance exercise. However, athletes routinely combine recovery interventions and little is known about the impact of a combined CJ and CWI protocol. Therefore, this study investigated the effects of combining CWI and CJ (a “cocktail” (CT)) on inflammation and muscle damage following a marathon. Methods Thirty-nine endurance trained males were randomly assigned to a placebo (PL), CWI, CJ or CT group before completing a trail marathon run. Muscle damage (creatine kinase (CK)), muscle function (maximal voluntary isometric contraction (MVIC), and inflammation (interleukin-6 (IL-6); C-reactive protein (CRP)) were measured at baseline, immediately post (only IL-6), 24h and 48h post marathon. Results There were no statistically significant differences between groups and no group x time interaction effects for any of the dependent variables. Confidence intervals (CI) illustrated that CT had unclear effects on inflammation (IL-6; CRP) and MVIC, but may have increased CK to a greater extent than PL and CJ conditions. Conclusion There is no evidence of an additive effect of CJ and CWI when the treatments are used in conjunction with each other. Conversely, combining CJ and CWI may lead to slightly increased circulating CK.